Formative E-assessment as a Tool for Promoting Competence-Based E-Learning in Universities: A Contextualized Perspective - GIKANDI, Joyce; NJUGUNA, Alice M. (KABARAK UNIVERSITY, 2020)
Ubiquitous Information communication technologies (ICT) and dynamics in today’s society (both disruptive and progressive changes) are increasingly driving adoption of e-learning models at all levels of education. Previous research has shown that the synergy between learner and assessment centered dimensions are antecedent to knowledge centeredness which is a key goal in higher education. This paper offers insights on how to address the key challenges facing Universities in implementation of competence-based learning through effective use of formative e-assessment in e-learning as a tool for fostering learner and assessment centeredness. The ultimate goal is to enhance understanding on effective integration of formative e-assessment in e-learning courses as a strategy for promoting competence-based education, while providing information that serve formative and summative purposes. It is also important to emphasize that use of formative e-assessment as a tool for assessment for learning (formative assessment) is an integral requirement for active and meaningful engagement particularly in e-learning settings. Formative assessment should be seamlessly integrated within teaching and learning processes; and it entails enabling adequate opportunities for continuous monitoring and assessment to inform formative feedback. However, such a focus has been lacking or inadequate based on what characterizes continuous assessment in many Universities e-learning settings. This implies that the validity of continuous assessment cannot be realized without purposeful focus on formative assessment and tailored feedback. This briefing paper therefore aims to offer better understanding on the role of formative e-assessment from a contextualized perspective as an important pedagogical strategy for enhancing e-learning. Contextualization implies paying attention to the unique needs of particular e-learning settings including ICT capacity, learners’ needs and experiences. Drawing from related literature and practical experiences, this paper offers best practices that need to be emphasized in applying formative e-assessment to promote learner and assessment centeredness that are desirable for achievement of envisaged core competences.
FULL TEXT
Keywords: Assessment for learning; E-learning; Embedded assessment; Transferable learning; Online assessment; Higher education